1999
DOI: 10.4141/s97-100
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction under grazing of annual and perennial forages

Abstract: Mapfumo, E., Chanasyk, D. S., Naeth, M. A. and Baron, V. S. 1999. Soil compaction under grazing of annual and perennial forages. . This study investigated the impact of heavy, medium and light grazing of meadow bromegrass an triticale on soil bulk density, relative compaction and penetration resistance. The study was conducted at Lacombe, Alberta, on a Orthic Black Chernozem of loam to silt loam texture. Sampling was conducted in fall 1995, spring 1996, fall 1996 and spring 1997. Core samples to a 15-cm depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 11 publications
3
37
0
2
Order By: Relevance
“…The pressure exerted by the trampling of heifers is lower than that of adult animals (Cantarutti et al, 2001), and the use of low stocking rates reduces the amount of trampling per unit soil surface, which in turn, reduces the impact of animal movement on soil density (Naeth et al, 1990). The probability that trampling by animal hoof occurs at the same location on the ground is increased in intensive pastoral systems with high stocking rates (Mapfumo et al, 1999), which in turn, increases the soil density values between 7 and 18% (Azenegashe et al, 1997). Second, the greater amount of litter under the tree canopy might have reduced the impact caused by animal movement in areas with intensive shade.…”
Section: Resultsmentioning
confidence: 99%
“…The pressure exerted by the trampling of heifers is lower than that of adult animals (Cantarutti et al, 2001), and the use of low stocking rates reduces the amount of trampling per unit soil surface, which in turn, reduces the impact of animal movement on soil density (Naeth et al, 1990). The probability that trampling by animal hoof occurs at the same location on the ground is increased in intensive pastoral systems with high stocking rates (Mapfumo et al, 1999), which in turn, increases the soil density values between 7 and 18% (Azenegashe et al, 1997). Second, the greater amount of litter under the tree canopy might have reduced the impact caused by animal movement in areas with intensive shade.…”
Section: Resultsmentioning
confidence: 99%
“…Greater amounts of fallen litter, and a lower stocking rate and density in the CG pasture may have reduced trampling effects on the soil. Other studies on Alberta pastures containing Orthic Black Chernozems with horizon sequence of Ah (> 15 cm), Bm 1 (14-35 cm), Bm 2 (35-53 cm), BCk and Ck (60 cm) (Walker et al 1991) found trampling associated with very heavy grazing caused significantly greater bulk densities in the top 7.5-cm (Naeth et al 1990;Chanasyk and Naeth 1995) and 2.5-3 cm of soil (Dormaar et al 1989;Mapfumo et al 1999). Differences in the depth of compaction in our study and others could be due to differences in soil type.…”
Section: Grazing Impacts On Soil Physical Propertiesmentioning
confidence: 97%
“…Differences in the depth of compaction in our study and others could be due to differences in soil type. Soil properties such as texture, organic matter, water content and other environmental conditions govern the degree to which compaction occurs (Mapfumo et al 1999). For example, our soil was Dark Gray Luvisolic with an organic matter content of 2.1% compared to as high as 9.5% in the study area of Mapfumo et al (1999).…”
Section: Grazing Impacts On Soil Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations